The Relationship Between Self-Control and Internet Addiction Among Students: A Meta-Analysis - Li, Shiqi; Ren, Ping; Chiu, Ming Ming; Wang, Chenxin; Lei, Hao (Frontiers in Psychology, 2021)
As past studies of self-control and Internet addiction showed mixed results, this meta-analysis of 83 primary studies with 80,681 participants determined whether (a) these students with less self-control had greater Internet addiction, and (b) age, culture, gender, Internet addiction measures, or year moderated these relations. We used a random-effects meta-analysis of Pearson product-moment coefficients r with Fisher’s z-transformation and tested for moderation with the homogeneity tests. Students with low self-control indicators often had higher Internet addiction, and those with high self-control indicators often had lower Internet addiction. The correlation between low self-control indicators and greater Internet addiction was stronger among undergraduates (18–22 years old) than among adolescents (10–17 years old). Furthermore, the negative link between a high self-control indicator and Internet addiction was greater (a) among students in East Asia than those in Western Europe/North America, (b) among males than females and (c) when using the Internet addiction measures GPIUS or IAT rather than CIAS. Hence, these results indicate a negative link between self-control and Internet addiction, and this link is moderated by age, culture, gender, and Internet addiction measure.